Assessment the capacity utilization of mature and immature area of replanting using time driven activity based costing - S. N. A. M., Zaini; Abu, Mohd Yazid (Penerbit UMP, 2020)
Malaysia is currently the world’s largest exporter of palm oil although it is the second-largest producer of the oil after neighboring Indonesia. There have recently been few concerns on this plantation. There are difficulties to understand the variance in the operations, the rate setting is inadequate to outlined the relation between the resources supplied and the capacity in operation, and finally the manager has no system to track the used and unused capacity. The aim of this work is to assess the capacity utilization of mature and immature area at replanting for a better accuracy. Time-driven activity-based costs (TDABC) is used because time efficiency can be calculated effectively. Furthermore, it also can precisely evaluate idle capacity and separately listing the resources being used and not used. This work considers a data in 2017 to develop the solution. This work found that in the mature area from the available capacity utilization, chipping has high insufficient capacity with RM-1931518.08, planting seedlings has high insufficient capacity with 805173.84 minutes and internal transport has high waste cost with RM45771.30. Meanwhile, in the immature area, planting seedlings has high insufficient capacity with 566934.84 minutes and RM-1621433.64, manuring has unused capacity with 66763.50 minutes and internal transport has high waste cost with RM29667.47.